Chemical pressure-induced anion order–disorder transition in LnHO enabled by hydride size flexibility - Yamashita, H; Broux, T; Kobayashi, Y; Takeiri, F; Ubukata, H; Zhu, T; Hayward, MA; Fujii, K; Yashima, M; Shitara, K; Kuwabara, A; Murakami, T; et al. (American Chemical Society, 2018)
While cation order–disorder transitions have been achieved in a wide range of materials and provide crucial effects in various physical and chemical properties, anion analogues are scarce. Here we have expanded the number of known lanthanide oxyhydrides, LnHO (Ln = La, Ce, Pr, Nd), to include Ln = Sm, Gd, Tb, Dy, Ho, and Er, which has allowed the observation of an anion order–disorder transition from the anion-ordered fluorite structure (P4/nmm) for larger Ln3+ ions (La–Nd) to a disordered arrangement (Fm3̅m) for smaller Ln3+ (Sm–Er). Structural analysis reveals that with the increase of Ln3+ radius (application of negative chemical pressure), the oxide anion in the disordered phase becomes too under-bonded, which drives a change to an anion-ordered structure, with smaller OLn4 and larger HLn4 tetrahedra, demonstrating that the size flexibility of hydride anions drives this transition. Such anion ordering control is crucial regarding applications that involve hydride diffusion such as catalysis and electrochemical solid devices.